Die letzten Tage des Baltischen Geschwaders - Taube, Georg Freiherr von (St. Petersburger Herold, 1907)
Fraktūras burti.
Letzten Tage des Baltischen Geschwaders
Keywords: Research Subject Categories::SOCIAL SCIENCES::Other social sciences::Military intelligence and security service; Krievijas-Japānas karš, 1904-1905; Cusimas kauja, 1905.; Jūras kaujas - Krievija - vēsture; Jūras kaujas - Japāna - vēsture; Russo-Japanese War, 1904-1905; Battle of Tsushima, 1905; Battle of the Sea of Japan, 1905; Naval battles - Russia - history; Naval battles - Japan - history; Russisch-Japanischer Krieg, 1904-1905; Seeschlacht bei Tsushima, 1905; Seeschlacht - Russland - Geschichte; Seeschlacht - Japan - Geschichte